Spermbots: A Promising Futuristic Innovation in Assisted Reproductive Technology - Bhat, Ghulam Rasool; Lone, Farooz Ahmad; Assad, Nafis Ibni (The Indian Journal of Animal Reproduction, 2023)
Spermbots are robotic sperms formed out of sperm cells conjugated to artificial microstructures, having potential  applications ranging from biomedical processes, drug delivery systems, in situ real time imagery and assisted reproduction.  The robotic sperm can act as an exploratory microdevice in biological networks. Incorporation of a biological entity like  sperm into microstructures under the environment of magnetic or electric fields helps in shape templating and carrying  chemotherapeutic agents to target sites. Besides its role in drug delivery systems, spermbots can potentially contribute in  combating infertility, especially in oligo-zoospermia and necro-zoospermia in males. Numerous checkpoints may impede  sperm cells to reach the oocyte in vivo. Spermbots bypass these sites and carry sperm to oocyte. Targeted delivery always  requires interventions of natural functional aspects of living systems. Sperm flagellum, being a biological motor in nature,  can be harnessed as a driving force in spermbots to ensure delivery of fertile sperm cells with impaired motile machinery to  the target. Moreover, the technology has a potential to unravel sperm migration patterns and understanding the processes  in vivo. After a review of documented literature on possible use of spermbot technology in assisted reproduction, we  hereby discuss the application of this new and innovative technology in humans and animals. The paper also highlights  certain shortfalls in the widespread application of this cargo delivery technology in assisted reproduction.
Keywords: Assisted reproduction; cargo; robotics; spermbot; micromotors